Characterisation of the evolution of pore structure with particle breakage during compaction. (August 2022) - Gou, Dazhao; An, Xizhong; Yang, Runyu
Graphical abstract: Highlights: The effect of particle breakage during compaction on compact structure was investigated. A watershed segmentation method was developed to characterise pore structure of compacts. Pore size and throat diameter decreased exponentially with reducing particle sizes. Spontaneous percolation dynamics of compacts was also affected by particle breakage. Relations between pore structure and percolation behaviour were established. Abstract: This work investigated the effect of particle breakage on the pore structure of compacts formed with the discrete element method. The watershed segmentation method was developed to quantify pore properties of the compacts. Results showed the pore size, throat diameter and throat length followed the log-normal distributions for all the compacts except for compacts in which significant particle breakage occurred. With particle breakage, the mean pore size and mean throat diameter decreased exponentially with reducing particle size. The pore structure was also explored through spontaneous interparticle percolation. Results showed that the residence time of the percolating particles followed the log-normal distributions. The coefficient of the radial dispersion increased linearly with depth for all compacts except for a compact with particle breakage. The relations between pore structure and percolation behaviour were established. With decreasing pore size and throat diameter, the mean residence time increased exponentially but the dispersion coefficient had a linear decrease.